Role of calprotectin in cardiometabolic diseases - Kruzliak, Peter; Novák, Jan; Novák, Miroslav; Fodor, George J (Cytokine & growth factor reviews, 2014)
Calprotectin represents an interesting peptide known to be involved in the pathophysiology of various inflammatory processes. Being secreted from activated neutrophils and monocytes under various conditions, it can also be found in the extracellular fluids and serve as a biomarker of ongoing inflammation, which property is currently used in the monitoring of inflammatory bowel diseases. Recent studies, however, suggest that calprotectin could serve as an important prognostic factor for cardiovascular and cardiometabolic diseases, since these are occurring on the basis of low-grade chronic inflammation. We assume that calprotectin may represent a useful marker in predicting the course of atherosclerotic process, coronary artery disease and acute coronary syndromes. Our review is focused on the importance of calprotectin in the diagnosis and prognostic stratification in the field of cardiometabolic risk.
Keywords: idiopatické střevní záněty; Obesity; Prognosis; nemoci koronárních tepen; ateroskleróza; Metabolic diseases; Leukocyte L1 Antigen Complex; Atherosclerosis; leukocytární L1-antigenní komplex; Coronary Artery Disease; Cardiovascular Diseases; prognóza; Humans; Myocardial infarction; biologické markery; Cardiovascular diseases; Risk; riziko; akutní koronární syndrom; Inflammatory Bowel Diseases; Biomarkers; Calprotectin; Acute Coronary Syndrome; kardiovaskulární nemoci; lidé